Thalidomide induces γ-globin gene expression through increased reactive oxygen species–mediated p38 MAPK signaling and histone H4 acetylation in adult erythropoiesis - Aerbajinai, Wulin (American Society of Hematology, 2007)
Although thalidomide has been shown to improve anemia in some patients with myelodysplastic syndromes and stimulates erythropoietin in patients with multiple myeloma, thalidomide's specific effects on γ-globin gene expression during erythroid differentiation have not been studied. Here, we investigated the effects of thalidomide on γ-globin gene expression and the involved signaling pathway using an ex vivo culture system of primary human CD34(+) cells. We found that thalidomide induced γ-globin mRNA expression in a dose-dependent manner, but had no effect on β-globin expression. We also demonstrated that intracellular reactive oxygen species (ROS) levels were increased by treatment with thalidomide for 48 hours (from day 3 to day 5). Western blot analysis demonstrated that thalidomide activated the p38 mitogen-activated protein kinase (MAPK) signaling pathway in a time- and dose-dependent manner and increased histone H4 acetylation. Pretreatment of cells with the antioxidant enzyme catalase and the intracellular hydroxyl scavenger dimethylthiourea (DMTU) abrogated the thalidomide-induced p38 MAPK activation and histone H4 acetylation. Moreover, pretreatment with catalase and DMTU diminished thalidomide-induced γ-globin gene expression. These data indicate that thalidomide induces increased expression of the γ-globin gene via ROS-dependent activation of the p38 MAPK signaling pathway and histone H4 acetylation.